An Innovative 500 W Alkaline Water Electrolyser System for the Production of Ultra-Pure Hydrogen and Oxygen Gases - Boguslaw Pierozynski; Tomasz Mikolajczyk; Boguslaw Wojciechowski; Mateusz Luba (Energies, 2021)
This paper communicates on an innovative, laboratory size alkaline water electrolyser (AWE) system, capable of efficiently producing ultra-pure hydrogen and oxygen gases. The system is composed of a zero-gap, bipolar-electrode stack, equipped with a polymer-based membrane, along with two drying columns for effective purification of H2 and O2 gaseous products. An optimal electrochemical efficiency of the electrolyser stack is provided through the employment of catalytically activated, extended surface-area nickel foam electrodes. Laboratory electrochemical examinations of the electrolyser included a series of galvanostatic AWE and alternating current (a.c.) impedance (single cell) experiments. Complementary examinations covered catalyst’s surface topography analysis by combined SEM (Scanning Electron Microscopy) and EDX (Energy Dispersive X-ray Spectroscopy) techniques along with chromatographic evaluation of the purity of hydrogen and oxygen products.